Discourse, politics and media in contemporary China - Cao, Qing; Tian, Hailong; Chilton, Paul A. (Paul Anthony) (Discourse approaches to politics, society, and culture, 2014)
This chapter discusses theoretical and methodological issues concerning doing critical discourse analysis in China. The authors believe that China's unique social, cultural and political context justifies an assumption that the Western originated paradigm of critical discourse analysis needs tailoring and appropriating when being applied in China. Starting from this assumption, the chapter discusses four issues relevant to discourse approach to the socio-political transformations in China: a 'wider' angle critical perspective, a research focus on the functionality of discourse, the emergent pu.